Applied Learning through the Management of Online Educational Resources - Charath, Pradeep; DeKoekkoek, Christina; Swift, Maris Stella (Star) (Archives of Business Research, 2018)
The purpose of the website, The Digital Workplace, was originally to educate individuals on how the increasing digitalization of the workplace affects business owners and employees, especially regarding the law. Since then the website has evolved to encompass many topics where technology and the law intersect, including cloud storage, privacy, free speech, and security. The site explains the law using cases as examples, with summaries, links to court documents, and videos. The site also explains technology with explanations on types of data storage, how to secure data, and data definitions. The website initially drew a lot of traffic from local students using it as a guide for their classes. When we received the Google AdWords Grant and began advertising the website usage increased. The Google AdWords Grant has given the website a global reach. Countries such as India, the Philippines, South Africa, and the United Kingdom are frequent visitors. One thing all these countries have in common is that they are all affected by the technological revolution and it impacts all their workplaces. The issue of how to manage a growing amount of data is universal along with the questions of privacy and security that come with any data management. In today’s world, cases involving technology are at the forefront of human rights; it is important to provide accessible information to people on the law in a format that they can understand.